Morphology and Molecular Confirmation of Contracaecum spp. in Fish - Ghasik J. Aqeele; Dhamyaa K. Kadhim; Firas Alali; Asaad SH. Alhesnawi; Taqi Mohammed Jwad Taher (Eastern Journal of Agricultural and Biological Sciences, 2024)
Contracaecum spp. is a parasite belonging to the Anisakidae family part of the nematode. It is characterized as a potential zoonotic parasite. In humans causing anisakiasis who consume undercooked seafood or raw infected with the larvae of this nematode. Planilizaabu specimens have been collected from Karbala city, Iraq (the local market). The survey on nematodes of Planilizaabu was done over eight months from May to December 2022. Prarsites were examined morphologically then confirmed the genus by molecular study for the presence of Contracaecum spp. A total of 493 fish were purchased and the incidence of larval type Contracaecum (L3) in the viscera was 21.50%. Morphological and molecular Confirmation of the parasite was done and the findings revealed that the prevalence rate of infection was greater in September and November than October. Molecularly, identification of Contracaecum spp. was conducted targeting 18S rRNA gene. Length and number of nematodes, as well as number of infected fish was significantly recorded. This study indicated that the presence of different intermediate hosts, organic and nonorganic contamination. This is the first molecular report identifying Contracaecum spp. in Razzaza Lake, Karbala province, Iraq. In the future, molecular markers may be an effective tool for determining the Contracaecum L3 larval species, different the life-cycle, and population structure and transmission pattern